Analysis of gene expression in Triticum aestivum L. cv. "Tugela DN" after Russian wheat aphid (Diuraphis noxia Mordvilco) infestation - Oberholster, A.M. (University of Pretoria, 2013)
Thesis (PhD (Genetics))--University of Pretoria, 2005.